معايير الجودة الشاملة في التعليم - سعيد, بن فرحات (Université de M'sila, 2020)
تهدف هذه الدراسة الى التعرف على موضوع معايير الجودة الشاملة في التعليم بعرض الجوانب النظرية المرتبطة بمعايير الجودة في التعليم و نظرا لما تعانيه معظم مؤسساتنا من سوء ادارة الموارد و ضعف المخرجات التعليمية مع صعوبة اصدار الاحكام التقويمية لعدم وجود معايير ومؤشرات واضحة المعالم تحدد لنا جودة التعليم .سلطنا الضوء في هدا المقال على هذا المفهوم. وخلصت الدراسة الي اقتنـــــــاع كامل بان جــــــودة التعليم تكون في وجود معايير محددة ودقيقة تصل في طموحها ودقتها الي درجــة توضيح ما يجب تعلمه واكتسابه والمستوى المطلوب للوصول اليه فـــــــي كل مجال من المجالات المرتبطـــــة بالعملـــية التعليميـــــة لتحسين النظام التعليمي بمختلف مكوناته البشرية والمادية والارتقاء بمستوى أدائه فماهي المعايير العالمية للجودة الشاملة في التعليم؟ وكيف ومتي نشأت وماهي فوائدها واغراضها وخصائصها؟ وماهي الجودة الشاملة؟ وماهي أنواع المعايير التي تستخدم لتوجيه ومتابعة المؤسسات والبرامج التربوية؟ ماهي المستويات المعيارية ومؤشرات الأداء؟ وكيف يمكن الوصول الى الغايات من خلال تطبيق المعايير العالمية لجودة التعليم؟؟ الكلمات المفتاحية: الجودة -جودة التعليم. الجودة الشاملة - المعايير-المنهاج -الكتاب المدرسي-التقويم Abstract : This study addresses and aims to identify the subject of total quality standards in education by presenting the theoretical aspects which related to quality standards in education and because of the weakness of educational outputs , we highlighted In this article international standards Where the overall quality in the field of education refers to a set of standards and procedures which aims to continuous improvement . The study concluded with full conviction that the quality of education lies in the existence of specific and precise standards which aims to clarify what should be learned and acquired and the level required to be reached in each of the areas related to the educational process to improve the educational system with its various human and material components and improve its performance . So What are the global standards of total quality in education ? How and when originated standards and what are its benefits, purposes and characteristics ? And what is the overall quality ? What are the types of standards that are used to guide and follow up educational institutions and programs ? What are the standard levels and performance indicators ? How to achieve the goals through the adoption of international standards for the quality of education ? Is it possible to employ total quality standards in our educational institutions with all their systems ? Keywords: Quality - Quality of Education - Total Quality - Standards - Curriculum - Textbook - Evaluation.
Keywords: الكلمات المفتاحية: الجودة -جودة التعليم. الجودة الشاملة - المعايير-المنهاج -الكتاب المدرسي-التقويم Keywords: Quality - Quality of Education - Total Quality - Standards - Curriculum - Textbook - Evaluation.